(untitled) (Research, Society and Development, 2021)
The consumption of 70% alcohols increased significantly worldwide after the pandemic of the new coronavirus (Covid-19). Due Consumption of 70% alcohols increased significantly worldwide after the pandemic of the new coronavirus (Covid-19). Due to the emergence and advance of this disease and its variants, it has become necessary that in all public and private establishments, such as commercial points, health service establishments, shops and traffic, 70% alcohol used as antiseptic is acquired and which proves to be very efficient in the fight of various parasites, fungi, viruses and bacteria, as this product was designed to eliminate 99.9% of these germs. The objective of this research was to identify the alcohol content and the physical-chemical characteristics of the alcohol commercialized in the center of Vitória da Conquista. This is an experimental research, containing 1 sample of 500mL of 10 different establishments randomly chosen located in the Centro neighborhood, the samples purchased will be analyzed in the laboratory of the Independent College of the Northeast - FAINOR. The methodology ut ...to the emergence and progress of this disease and its variants, it became necessary that in all public and private establishments, such as commercial points, health services establishments, stores and traffic, 70% alcohol used to be purchased as an antiseptic and shown to be quite efficient in combating several parasites, fungi, viruses and bacteria, since this product was designed to eliminate 99.9% of these germs. The objective of this project is to identify the alcohol content and the physical and chemical characteristics of the alcohol sold in the center of Vitória da Conquista. A methodology with experimental research will be used, containing 1 500mL sample from 10 different establishments chosen randomly located in the Centro neighborhood, the purchased samples will be analyzed in the laboratory of Faculdade Independente do Nordeste - FAINOR.